2005
DOI: 10.1021/ef0501086
|View full text |Cite
|
Sign up to set email alerts
|

Kerogen Chemistry 4. Thermal Decarboxylation of Kerogens

Abstract: Infrared spectra confirm that, when heated to 200 °C, Bakken kerogens form anhydrides from carboxylic acids. The anhydrides in turn thermally decompose at temperatures below 250 °C. The thermal production of CO, the absence of CO2, and the low temperature of the anhydride decomposition are all consistent with a radical chain mechanism initiated by a kerogen radical. Anhydride decomposition occurs by addition of a radical to the anhydride carbonyl to form an ester and to liberate an acyl radical that rapidly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…However, because carboxyl groups cannot easily migrate in kerogen to find a partner for anhydride formation, most carboxyl groups in kerogen are likely to form carboxylate anions . The next step recognized in the thermal evolution of carboxylic acid anhydrides is decarboxylation resulting in a chain reaction that forms alkyl radicals and esters (Ashida et al, 2005). This reaction has been found to occur in shales when heated to 200À250ºC (Ashida et al, 2005), similar to the experimental conditions in this study.…”
Section: Effect Of Dehydration Temperature On Bulk-rock Cec Measurementsupporting
confidence: 78%
See 1 more Smart Citation
“…However, because carboxyl groups cannot easily migrate in kerogen to find a partner for anhydride formation, most carboxyl groups in kerogen are likely to form carboxylate anions . The next step recognized in the thermal evolution of carboxylic acid anhydrides is decarboxylation resulting in a chain reaction that forms alkyl radicals and esters (Ashida et al, 2005). This reaction has been found to occur in shales when heated to 200À250ºC (Ashida et al, 2005), similar to the experimental conditions in this study.…”
Section: Effect Of Dehydration Temperature On Bulk-rock Cec Measurementsupporting
confidence: 78%
“…The next step recognized in the thermal evolution of carboxylic acid anhydrides is decarboxylation resulting in a chain reaction that forms alkyl radicals and esters (Ashida et al, 2005). This reaction has been found to occur in shales when heated to 200À250ºC (Ashida et al, 2005), similar to the experimental conditions in this study. Thus, negatively charged sites produced by thermal alteration of kerogen may be responsible for attracting additional cations from the solution.…”
Section: Effect Of Dehydration Temperature On Bulk-rock Cec Measurementsupporting
confidence: 78%
“…Radical mechanisms may be inferred from electron spin resonance (ESR) studies of brown coal; such studies have shown that increasing the temperature caused the loss of oxygen functional groups and the small concentrations of paramagnetic centers at 300 °C increased at ∼400 °C, reaching maximum radical densities around 550 °C . While studies of the thermal decarboxylation of kerogens indicated that the thermal production of CO may also occur via a radical chain mechanism, the thermal behavior of the well-characterized polymer poly(methacrylic acid) has been reported to form CO 2 and also H 2 O, CO 2 , and CO by mechanisms that include the formation and decomposition of anhydrides; similar chemistry may produce CO 2 and H 2 O from low-rank coals, and this has been considered to lead to cross-linking . Additionally, studies involving the pyrolysis of dicarboxylic acids have shown that decarboxylation occurred primarily by an acid-promoted ionic mechanism, with protonation by a second carboxylic acid .…”
Section: Introductionmentioning
confidence: 99%
“…The Kimmeridge kerogen shows a strange increase in C-H intensity between 200 and 250 °C that we have previously discussed and that we plan to examine further. 23 There is a lowtemperature loss of hydrocarbons below 200 °C, presumably by evaporation. There is no evidence for the presence of anhydrides.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently published the observation that kerogens form anhydrides in an endothermic process when they are heated at temperatures below 200 °C . These anhydrides then decompose by a radical chain reaction initiated by attack of a kerogen radical on the anhydride carbonyl oxygen. , The products are CO and an ester. Thus, kerogens can decarboxylate at low temperatures in a two-step process (Scheme ) that yields a kerogen ester, water, and CO. Because this process proceeds through anhydride formation, it will not occur in water-wet systems.…”
Section: Introductionmentioning
confidence: 99%